2018
DOI: 10.1002/advs.201801572
|View full text |Cite
|
Sign up to set email alerts
|

Design of Single‐Molecule Multiferroics for Efficient Ultrahigh‐Density Nonvolatile Memories

Abstract: It is known that an isolated single‐molecule magnet tends to become super‐paramagnetic even at an ultralow temperature of a few Kelvin due to the low spin switching barrier. Herein, single‐molecule ferroelectrics/multiferroics is proposed, as the ultimate size limit of memory, such that every molecule can store 1 bit data. The primary strategy is to identify polar molecules that possess bistable states, moderate switching barriers, and polarizations fixed along the vertical direction for high‐density perpendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 45 publications
(110 reference statements)
0
33
0
Order By: Relevance
“…After removing the E- and H-fields, the FL magnetization rotates 180° and stabilizes in the antiparallel state because of the magnetic shape anisotropy as shown in Figure 9 H. Hence, the E-field-induced magnetoelastic anisotropy dominates over the magnetic shape anisotropy (see details in Figure S15 in the supplemental information ) and helps the magnetization overcome the energy barrier to facilitate the 180° reversal of the FL ( Hu et al., 2011 ). Both the aforementioned experimental and simulation results firmly elucidate that the angle-dependent magnetic switching, the TMR modulation and non-volatile and reversible 180° magnetization switching by the E-fields should result from competition among the E-field-induced magnetoelastic anisotropy, the magnetic shape anisotropy, and the unidirectional anisotropy introduced from the external small H-field in the hybrid, facilitating energy-efficient spintronic devices ( Yang et al., 2019 ). The simulated moments of the RL are hardly influenced by due to the strong exchange bias field, which is consistent with the experimental results in Sec.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…After removing the E- and H-fields, the FL magnetization rotates 180° and stabilizes in the antiparallel state because of the magnetic shape anisotropy as shown in Figure 9 H. Hence, the E-field-induced magnetoelastic anisotropy dominates over the magnetic shape anisotropy (see details in Figure S15 in the supplemental information ) and helps the magnetization overcome the energy barrier to facilitate the 180° reversal of the FL ( Hu et al., 2011 ). Both the aforementioned experimental and simulation results firmly elucidate that the angle-dependent magnetic switching, the TMR modulation and non-volatile and reversible 180° magnetization switching by the E-fields should result from competition among the E-field-induced magnetoelastic anisotropy, the magnetic shape anisotropy, and the unidirectional anisotropy introduced from the external small H-field in the hybrid, facilitating energy-efficient spintronic devices ( Yang et al., 2019 ). The simulated moments of the RL are hardly influenced by due to the strong exchange bias field, which is consistent with the experimental results in Sec.…”
Section: Resultsmentioning
confidence: 73%
“…Therefore, a minimum magnetic field (switching field) is a prerequisite to realize a 180° magnetic switching. Such a large reduction in switching field is highly beneficial to energy-efficient spintronic devices ( Liu, et al., 2011 ; Yang, et al., 2019 ). The magnetic switching can be achieved by the E-field (∼6 kV/cm) with a relatively small H-field (∼12 Oe) bias, as illustrated in Figure 3 F. Such a tunability can be comparable with that (−75% with a 400 V gate voltage) in the PMN-PT (011)/Ta/Ru/IrMn/CoFe/Ru/CoFeB/MgO/CoFeB/Ta/Ru hybrid device with a lateral electric field configuration ( Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in multiferroic MXene, VS 2 , MoN 2 bilayers 76 and ultrathin CuCrS 2 or CuCrSe 2 , 77 it was found that the magnetizations can be reversed by the FE switching owing to strong magnetoelectric coupling. Furthermore, when metal porphyrin (MP) molecule is intercalated in 2D materials like bilayer MoS 2 or FM CrI 3 , the magnetization, spin distribution or direction of single MP molecules can be switched upon FE reversal 46 …”
Section: Ferroelectric Controllable Applications In Physics and Chemimentioning
confidence: 99%
“…The ability to reversibly switch between two or more states, aside from being fascinating from a fundamental chemistry perspective, is an important feature for practical applications in sensing, displays, molecular electronics, and in particular, data storage. [1][2][3][4] While the miniaturization of silicon-based components faces major obstaclessuperparamagnetism, quantum effects, and heat, for example [4][5][6] switchable molecules offer the potential to store data at the molecular scale, or serve as individual electronic or spintronic components in a device. Meanwhile, the vivid color changes that often accompany the transition between states lend these systems the potential for use as molecular scale components in chromic-based sensors and displays.…”
Section: Introductionmentioning
confidence: 99%